2017
DOI: 10.3396/ijic.v13i2.007.17
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors for Hepatitis B and C among health care workers

Abstract: Health care workers (HCWs) are at high risk of exposure to hepatitis B virus (HBV) and hepatitis C virus (HCV) transmission due to injuries and frequency of exposure. We aimed to assess HBV/HCV seroprevalence among nurses and housekeepers in Beni-Suef University Hospital, and to identify possible risk factors.A cross sectional study was conducted from March to July 2016 using a self-administered questionnaire. A blood sample was withdrawn from each participant and tested for hepatitis B surface antigen (HBsAg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(21 reference statements)
1
8
0
Order By: Relevance
“…In 1991, the World Health Organization recommended that all countries should implement an anti-HBV vaccine in their national vaccination program by 1997 [ 20 , 21 ]. Given HCWs elevated risk of HBV infection, and the related risks of infected HCWs transmitting the virus to uninfected patients, the strength of occupational protection of HCWs by vaccination should be increased aggressively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1991, the World Health Organization recommended that all countries should implement an anti-HBV vaccine in their national vaccination program by 1997 [ 20 , 21 ]. Given HCWs elevated risk of HBV infection, and the related risks of infected HCWs transmitting the virus to uninfected patients, the strength of occupational protection of HCWs by vaccination should be increased aggressively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately, 30% of health care workers having hepatitis C infection was reported from one of the teaching hospital at Abbottabad, Pakistan (Sarwar et al, 2007). Along with this, the unclean dental equipment is common in almost every dental clinic of Pakistan (Ali et al, 2009a).…”
Section: Discussionmentioning
confidence: 99%
“…Being at risk, health care workers were screened and 2.4 to 5.6% were found infected by HBV and HCV and co-infection was found in 3.2% cases. 36 A very high proportion of HCV were affected by hepatitis B and C when evaluated in Jamshoro, Sindh. 37 Women were screened for hepatitis B and C during pregnancy in various studies, and the prevalence of hepatitis C was found much higher than hepatitis B (2.5–13.3% vs 1.2–3%) ( Table 5 ).…”
Section: Blood Borne Pathogens: Hepatitis B C and Dmentioning
confidence: 98%